Strategy and programme for ILRI information resources. 1998-2010 - International Livestock Research Institute (International Livestock Research Institute, 1998)
This document is divided in seven chapters. The first chapter discusses ILRI Information Services since the founding of ILCa in 1975. Stakeholders, beneficiaries and users of ILRI Information Services are presented in a tabular form and organisational chart of ILRI's Information Services within the programme to strengthen partnerships with NARS is also shown. The second chapter deals with SWOT analysis of ILRI Information Services with particular reference to strengths, weaknesses, opportunities and threats. ILRI as a knowledge broker is the topic of chapter 3 while proposed strategy, 1998-2010 is highlighted in chapter 4. In this chapter information services and their relation to training and publishing is illustrated, information resources is assessed and logical framework for ILRI information resources 1998-2010 is presented in a tabular form. Other topics of discussion in this chapter inlcude Inter-disciplinary Group for Knowledge and Information Products and Services, ILRI and othe rproviders of information, document transfer between Addis and Nairobi, integrated library management, non-conventional literature, Geographic Information Systems, and ILRi public awareness activities. The last three chapters are on partnerships; staffing, organisational structure and outline schedule for implementation; and funding.